1996
DOI: 10.1093/hmg/5.9.1311
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type-1 and spinobulbar muscular atrophy gene products interact with glyceraldehyde-3-phosphate dehydrogenase

Abstract: Spinocerebellar ataxia type1 (SCA1) is one of several neurodegenerative disorders caused by expansions of translated CAG trinucleotide repeats which code for polyglutamine in the respective proteins. Most hypotheses about the molecular defect in these disorders suggest a gain of function, which may involve interactions with other proteins via the expanded polyglutamine tract. In this study we used ataxin-1, the SCA1 gene product, as a bait in the yeast two-hybrid system and identified the glycolytic enzyme gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(66 citation statements)
references
References 37 publications
0
66
0
Order By: Relevance
“…33 A similar lack of correlation between the AR protein expression levels and pathological involvement is seen in the nervous system; neurons in Onuf's nuclei and Purkinje cells, for example, express a relatively large amount of AR protein, 33 but these neurons are not affected in SBMA. The underlying mechanism that induces the selective formation of nuclear inclusions in neural as well as nonneural tissues remains undetermined; specific factors may be present only in the tissues with the nuclear inclusions, such as a protease that cleaves the N-terminal portion from the full-length AR protein, or specific proteins that interact with the mutant AR, as demonstrated in SCA1 23,26 and HD, 21,22,24,25 may contribute to the cell type-specific formation of the nuclear inclusions. Alternatively, a degenerative process leading to apoptotic cell death with activation of a protease such as caspase 3 may be involved in the formation of nuclear inclusions as proposed in HD, DRPLA, MJD, and SBMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 A similar lack of correlation between the AR protein expression levels and pathological involvement is seen in the nervous system; neurons in Onuf's nuclei and Purkinje cells, for example, express a relatively large amount of AR protein, 33 but these neurons are not affected in SBMA. The underlying mechanism that induces the selective formation of nuclear inclusions in neural as well as nonneural tissues remains undetermined; specific factors may be present only in the tissues with the nuclear inclusions, such as a protease that cleaves the N-terminal portion from the full-length AR protein, or specific proteins that interact with the mutant AR, as demonstrated in SCA1 23,26 and HD, 21,22,24,25 may contribute to the cell type-specific formation of the nuclear inclusions. Alternatively, a degenerative process leading to apoptotic cell death with activation of a protease such as caspase 3 may be involved in the formation of nuclear inclusions as proposed in HD, DRPLA, MJD, and SBMA.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is thought to be a toxic gain of function of the mutant gene products 19,20 involving cell-specific proteinprotein or protein-nucleic acid interactions with the products of the mutant genes. [21][22][23][24][25][26] Intranuclear inclusions of the mutant proteins have recently been documented in the neurons of HD, 27,28 26 In all of these disorders, the inclusions can be labeled with antibodies (Abs) to the disease protein product and to ubiquitin. The inclusions are so far detected in the neurons of the affected brain areas of each disease, and rarely in other brain regions, [27][28][29][30][31][32] despite the ubiquitous expression of the disease gene product.…”
mentioning
confidence: 99%
“…When initially cloned, ARNIP was not represented in protein databases; its nucleotide sequence was, however, homologous to entries in EST databases, uncharacterized GenBank clones and to human and Drosophila genomic sequences. In addition, ARNIP is distinct from other known AR N terminal-interacting proteins: AES (amino-terminal enhancer of split; Yu et al (2001)); ARA24 (Ran, a nuclear Ras-related G-protein; ); ARA160 (HIV-1 TATA element modulatory factor, TMF; ); caveolin-1 (Lu et al 2001); CAK (cdk activating kinase; Lee et al (2000)); FHL2 (four and half LIM domain protein 2; Müller et al (2000)); glyceraldehyde-3-phosphate dehydrogenase (Koshy et al 1996); PITALRE (a kinase subunit of positive elongation factor b, P-TEF-b; Lee et al (2001)); PQBP-1 (polyGln-protein-1; Iwamoto et al (2000)); RB (retinoblastoma; Yeh et al (1998)); SHP (short heterodimer partner; Gobinet et al (2001)) and TR4 (testicular orphan receptor-4; Lee et al (1999)). …”
Section: Discussionmentioning
confidence: 99%
“…Expansion of poly-Q repeats has been suggested to convey a "toxic gain of function" to the affected proteins. Huntingtin (the normal gene product of HD), DRPLA protein, androgen receptor, ataxin-1 (the normal gene product of SCA-1), and poly-Q constructs bind strongly to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) (1,2). It was suggested that interactions of extended poly-Q domains may disrupt the activity of GAPDH and interfere with energy metabolism (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Huntingtin (the normal gene product of HD), DRPLA protein, androgen receptor, ataxin-1 (the normal gene product of SCA-1), and poly-Q constructs bind strongly to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) (1,2). It was suggested that interactions of extended poly-Q domains may disrupt the activity of GAPDH and interfere with energy metabolism (1,2). However, recent work from our laboratory showed that E. coil glutathione $-transferase constructs containing poly-Q inserts of various lengths (GSTQ n where n = 0, 10, 62 or 81 ) have no effect on the activity of GAPDH (6).…”
Section: Introductionmentioning
confidence: 99%